The promotion of good governance and democracy in the context of regional integration in Africa - Rwinkoko, Patrick (Department of Commercial Law, 2026)
Africa is one of the continents of the world that has embraced the democratisation process. In the last century when the rest of the world moved towards democracy and development, Africa remained a predominantly military or semi military-controlled continent ruled mostly by non-democratic and dictatorial governments. The formation of the Organisation for (OAU), now the African Union (AU) was the first step. towards promoting continental unity. The adoption of the Constitutive Act was a decisive step, showing that African states were not only conveniently changing the name of their continental organization, but indeed giving it a radically new vision and mission, and a set of clearly defined objectives and responsibilities. Some of the AU objectives are to accelerate the political and socio-economic integration of the continent, promote peace, security, and stability on the continent and the respect for democratic principles, human rights, the rule of law and good governance. These led to the creation of different Regional Economic Communities (RECs) as role players in the process of the unification of the continent, but more particularly the way of promoting principles of good governance and democracy and the respect of the rule of law. If the rule of law is a universal principle, then supporting the rule of law is not necessarily imposing foreign ideas on a society. The challenge is to find ways in which a society may govern itself under the rule of law, using an approach that reflects the values and norms of that society.